Amidyl Radicals by Oxidation of α‐Amido‐oxy Acids: Transition‐Metal‐Free Amidofluorination of Unactivated Alkenes. (28th June 2018) - Jiang, Heng; Studer, Armido
Abstract: A three‐component transition‐metal‐free amidofluorination of unactivated alkenes and styrenes is presented. α‐Amido‐oxy acids are introduced as efficient and easily accessible amidyl radical precursors that are oxidized by a photoexcited organic sensitizer (Mes‐Acr‐Me) to the corresponding carboxyl radical. Sequential CO2 and aldehyde/ketone fragmentation leads to an N‐centered radical that adds to an alkene. Commercial Selectfluor is used to trap the adduct radical through fluorine‐atom transfer. The transformation features by high functional‐group tolerance, broad substrate scope, and practical mild conditions. Mechanistic studies support the radical nature of the cascade.